Assessment of prescription profile of pregnant women visiting antenatal clinics. - Eze UI; Eferakeya AE; Oparah AC; Enato EF (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Managing medical complications in pregnancy is a challenge to clinicians. Objectives: This study profiled some disease and prescription patterns for pregnant women attending antenatal clinics (ANCs) in Nigeria. A risk classification of the medicines was also determined. Methods: Medical case files of 1,200 pregnant women attending antenatal clinics of 3 health facilities in Benin City, Nigeria were investigated. Disease pattern was determined from their diagnoses. The prescription pattern was assessed using WHO indicators, and the United States Food and Drug Administration classification of medicines according to risk to the foetus. Results: A total of 1,897 prescriptions of the 1,200 pregnant women attendees during the period under review were evaluated. Results indicated that malaria 554 (38%) was the most prevalent disease, followed by upper respiratory tract infections (URTIs, 13%) and gastrointestinal disturbances (GIT, 12%). The average number of drugs prescribed per encounter was found to be 3.0, and 2,434 (43%) of medicines were prescribed by generic name. Minerals/ Vitamins 2,396 (42%) were the most frequently prescribed medicines, and antibiotics occurred in 502 (8.8%) of the total medicines. Of all medicines prescribed, 984 (17%) were included in the foetal risk category C and 286 (5%) in category D. Conclusion: The study concluded that malaria fever occurred most frequently followed by URTIs and GIT disturbances among the pregnant women. Minerals, vitamins and to a less extent anti-malarials topped the list of the prescribed medicines. The average number of medicines per encounter was much higher than WHO standards. The occurrence of contraindicated medicines was low.